Multi-wavelength fiber laser in the S-band region using a Sagnac loop mirror as a comb generator in an SOA gain medium - Zulkifli, M.Z.; Hassan, N.A.; Awang, N.A.; Ghani, Z.A.; Harun, Sulaiman Wadi; Ahmad, Harith (John Wiley & Sons, 2010)
A simple design of multi-wavelength generation in the S-band region of the optical network transmission is proposed. The design consists of broad-band fiber Bragg grating (BB-FRG). which acts as a filter to enhance operation in the S-band region. A Sagnac loop mirror (SLM) is used to generate multiple wavelength oscillations in the ring cavity. The output consists of 60 lasing wavelengths oscillating simultaneously between 1464 nm and 1521 nm with a spacing of 0.92 nm and an output linewidth of 066 nm